Antifungal effects of zinc nanoparticles green synthesized by Lavandula angustifolia extract, alone and combined with nystatin against Candida albicans, a major cause of oral candidiasis - Saman Nasiri; Hossein Mahmoudvand; Mojtaba Shakibaei; Seyyed Amir Hossein Mousavi; Asghar Sepahvand (Shahrekord University of Medical Sciences, 2022)
Introduction: This work aimed to determine the antifungal effects of zinc nanoparticles (ZnNPs) green synthesized by Lavandula angustifolia extract, alone and along with nystatin against Candida albicans. Methods: ZnNPs were green synthesized with L. angustifolia extract by microwaves method. Antifungal effects of ZnNPs were studied by measuring the minimum inhibitory concentrations (MICs) and minimum fungicidal concentrations (MFCs) using the broth microdilution method based on the modified M27-A3 protocol on yeasts, recommended by the Clinical and Laboratory Standards Institute (CLSI). Effects of green synthesized ZnNPs against human normal fibroblast-like Gingiva (HGF1-PI1) and human epithelial-like oral cancer (KB) cell lines were studied by MTT (3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) method. Results: The ZnNPs showed a spherical shape with some grains of different lengths. The best levels of MIC and MFC were connected to the combination of ZnNPs + nystatin with values of 0.204 and 0.250 μg/mL, respectively. The combination of ZnNPs with nystatin compared to the nystatin group had a significantly better antifungal effect on C. albicans (P < 0.001). The 50% cytotoxic concentrations of ZnNPs against normal (HGF1-PI1) and cancer (KB) cells were 172.3 and 83.2 μg/mL, respectively. Conclusion: We found that ZnNPs plus nystatin had a potent antifungal effect against C. albicans. These findings indicated the cytotoxic effects of green synthesized ZnNPs on cancerous cells, whereas they were nontoxic for normal cells. Additional studies are necessary to explain the accurate mechanism and toxicity.